2019
DOI: 10.1016/j.jpag.2019.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiological Findings of Vulvovaginitis in Prepubertal Girls

Abstract: Participants: Fifty-two prepubertal girls aged 1-9 years diagnosed with vulvovaginitis, and 42 age-matched healthy controls. Interventions and Main Outcome Measures: Samples for microbiological culture were collected using sterile cotton swabs from the introitus and the lower third of the vagina from all study participants. Microbiological findings were analyzed according to bacteria type and intensity of growth. Results: Most of the vaginal microbiological swab results were positive for bacterial growth: 47 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…The cases that are still reported, even in the vaccinated populations, are probably caused mostly by non-encapsulated or untypeable strains of H. influenzae . The low rate detected in our study may be attributed to the implementation of the vaccine from 1995 in Greece, and this result is in agreement with reports from different countries where vaccination is available [ 13 , 19 , 20 ]. In contrast, a recent report identified H. influenzae as the second most common pathogen in preschool-aged girls with a prevalence of 27.2% while McGreal and Wood reported it as the third most common pathogen with a prevalence of 10% in prepubertal girls [ 12 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The cases that are still reported, even in the vaccinated populations, are probably caused mostly by non-encapsulated or untypeable strains of H. influenzae . The low rate detected in our study may be attributed to the implementation of the vaccine from 1995 in Greece, and this result is in agreement with reports from different countries where vaccination is available [ 13 , 19 , 20 ]. In contrast, a recent report identified H. influenzae as the second most common pathogen in preschool-aged girls with a prevalence of 27.2% while McGreal and Wood reported it as the third most common pathogen with a prevalence of 10% in prepubertal girls [ 12 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…It is a common pathogen for the upper respiratory tract, and thus, children who are colonized with S. pyogenes are at increased risk of streptococcal vulvovaginitis since this pathogen can be easily transferred in the genital area [ 23 ]. Although not the commonest pathogen in our study population, the prevalence of S. pyogenes was similar with recent reports [ 12 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Shigella is a rare cause of vulvovaginitis; therefore, it is not routinely tested for on cultures and must be ordered specifically. The most common vulvovaginitis bacteria tested for in children include S. pyogenes , H. influenzae , Escherichia coli , Candida albicans and Neisseria gonorrhoeae 1 3 13 14 . Shigella may go undetected in routine laboratory assays due to limited viability outside the human body and improper culturing techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Prevotella , not Lactobacillus , was the predominant vaginal species in healthy prepubertal girls, although there is evidence that several species of Prevotella found in the vagina are associated with bacterial vaginosis (BV) [ 10 ]. Compared with the HVS group, the relative abundance of Granulicatella , Streptococcus , and Haemophilus , which have been found to be closely related to vaginal infection, was enriched in the VVS group [ 11 , 12 ]. It has been reported that fecal flora is a significant cause of vulvovaginitis in prepubertal girls.…”
Section: Discussionmentioning
confidence: 99%